EFFECTIVENESS OF USING THE TIKTOK APPLICATION AS A DIGITAL DAKWAH MEDIA FOR GENERATION Z (STUDY OF TIKTOK ACCOUNTS @Basyasman00) - Rochmah, Nur Hafifah (UIN Kiai Ageng Muhammad Besari Ponorogo, 2022)
Abstract: In this modern era, the existence of the use of social media has a significant influence on people's daily lives, especially Generation Z. This paper aims to determine the extent of the role of the Tiktok application as one of the platforms favored by Generation Z on the spread of values. Islamic valuesthrough the creator of the da'wah Husain Basyaiban. This research is included in the type of library research with a qualitative descriptive approach. The research data was obtained through direct observation on the TikTok account @Basyasman00 as well as documentation on uploaded posts to see the activities of netizens including the number of followers, likes, comments, shares and video views. Furthermore, the data collected was analyzed using a content analysis approach (content analysis). The results show that da'wah through the TikTok application is quite effective in reaching generation Z. The TikTok application is a surefire way to spread Islamic values today, especially for generation Z because of the great interest in knowledge about religion which is presented in a unique, interesting, and interesting way. and contemporary. The content that is in great demand by Gen Z is about solving the current issues that are booming as well as light topics that are closely related to the daily lives of teenagers. Keywords: TikTok, Generation Z, Digital Da'wah, Husain Basyaiban.